Analisis Manajemen Risiko Pelaksanaan Pembangunan Jalan Tol (Studi Kasus : Proyek Pembangunan Jalan Tol Bekasi - Cawang - Kampung Melayu) - Nia Rahmawati; Andi Tenrisukki Tenriajeng (Rekayasa Sipil, 2020)
Construction of highway will increase the economy but it can’t be separated from risks. The purpose of this study is to analyze the risks at the stage of the implementation of highway construction and mitigation to minimize the negative impact. The study uses Descriptive Analysis and Analytical Hierarchy Process in highway construction of Bekasi-Cawang-Kampung Melayu. Based on the result of analysis, the most dominant risk in aspect: 1)Politics:change of structure in government; 2)Environment: land acquisition; 3)Economy: owner’s late payment; 4)Finance:high overhead; 5)Nature: weather delay; 6)Project: material delivery delay; 7)Human: fatigue caused overtime; 8)Technical: nonconformity of volume in contract and reality; 9)Criminal: loss of materials and equipment; 10)Safety: lack of worker awareness. Then the dominant risk will be mitigated.